Formative assessment, learning data analytics and gamification : in ICT education - Caballe, Santi, 1967-; Clariso, Robert (Intelligent data centric systems., 2016)
Discussing the challenges associated with assessing student progress given the explosion of e-learning environments, this book shows educators how to effectively garner intelligent data from online educational environments that combine assessment and gamification. --